Drought history affects grassland plant and microbial carbon turnover during and after a subsequent drought event. (24th May 2016) - Fuchslueger, Lucia; Bahn, Michael; Hasibeder, Roland; Kienzl, Sandra; Fritz, Karina; Schmitt, Michael; Watzka, Margarete; Richter, Andreas
Summary: Drought periods are projected to become more severe and more frequent in many European regions. While effects of single strong droughts on plant and microbial carbon (C) dynamics have been studied in some detail, impacts of recurrent drought events are still little understood. We tested whether the legacy of extreme experimental drought affects responses of plant and microbial C and nitrogen (N) turnover to further drought and rewetting. In a mountain grassland, we conducted a 13 C pulse‐chase experiment during a naturally occurring drought and rewetting event in plots previously exposed to experimental droughts and in ambient controls (AC). After labelling, we traced 13 C below‐ground allocation and incorporation into soil microbes using phospholipid fatty acid biomarkers. Drought history (DH) had no effects on the standing shoot and fine root plant biomass. However, plants with experimental DH displayed decreased shoot N concentrations and increased fine root N concentrations relative to those in AC. During the natural drought, plants with DH assimilated and allocated less 13 C below‐ground; moreover, fine root respiration was reduced and not fuelled by fresh C compared to plants in AC. Regardless of DH, microbial biomass remained stable during natural drought and rewetting. Although microbial communities initially differed in their composition between soils with and without DH, they responded to the natural drought and rewetting in a similar way: gram‐positive bacteria increased, while fungal and gram‐negative bacteria remained stable. In soils with DH, a strongly reduced uptake of recent plant‐derived 13 C in microbial biomarkers was observed during the natural drought, pointing to a smaller fraction of active microbes or to a microbial community that is less dependent on plant C. Synthesis . Drought history can induce changes in above‐ vs. below‐ground plant N concentrations and affect the response of plant C turnover to further droughts and rewetting by decreasing plant C uptake and below‐ground allocation. DH does not affect the responses of the microbial community to further droughts and rewetting, but alters microbial functioning, particularly the turnover of recent plant‐derived carbon, during and after further drought periods. Abstract : Drought history can induce changes in above‐ vs. below‐ground plant N concentrations and affect the response of plant C turnover to further droughts and rewetting by decreasing plant C uptake and below‐ground allocation. Drought history does not affect the responses of the microbial community to further droughts and rewetting, but alters microbial functioning, particularly the turnover of recent plant‐derived carbon, during and after further drought periods.